The notebook : a novel - Sparks, Nicholas (New York : Warner Books, 1998)
"At thirty-one, Noah Calhoun, back in coastal North Carolina after World War II, is haunted by images of the girl he lost more than a decade earlier. At twenty-nine, socialite Allie Nelson is about to marry a wealthy lawyer, but she cannot stop thinking about the boy who long ago stole her heart. Thus begins the story of a love so enduring and deep it can turn tragedy into triumph, and may even have the power to create a miracle."--Cover.
National College of Business and Arts
Keywords: Man-woman relationships -- North Carolina -- Fiction; Love stories